2020
DOI: 10.1590/1806-9282.66.12.1645
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of plasma copeptin level for diagnosis and mortality of pulmonary embolism

Abstract: SUMMARY OBJECTIVE: Early diagnosis and risk stratification may provide a better prognosis in pulmonary embolism (PE). Copeptin has emerged as a valuable predictive biomarker in various cardiovascular diseases. The aim of this study was to determine the levels of copeptin in patients with acute PE and to evaluate its relationship with disease severity and PE-related death. METHODS: Fifty-four patients and 60 healthy individuals were included in this study. Copeptin concentrations and right ventricular dysfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
3
4
0
Order By: Relevance
“…Additionally, ROC curve analysis revealed a cut-off value for copeptin of 7.96 pmol/L with a sensitivity of 80.4% and a specificity of 73.6%. Our results are in concordance with previously published papers where copeptin presented with a 68.1-71.9% sensitivity and a 83.7-85% specificity for acute PE [14,19]. When compared with D-dimers, the diagnostic power of copeptin is slightly lower, presenting with an AUC of 0.800 (95% CI 0.728-0.873) vs. the AUC of 0.908 (95% CI 0.851-0.965, p < 0.001) for D-dimers.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, ROC curve analysis revealed a cut-off value for copeptin of 7.96 pmol/L with a sensitivity of 80.4% and a specificity of 73.6%. Our results are in concordance with previously published papers where copeptin presented with a 68.1-71.9% sensitivity and a 83.7-85% specificity for acute PE [14,19]. When compared with D-dimers, the diagnostic power of copeptin is slightly lower, presenting with an AUC of 0.800 (95% CI 0.728-0.873) vs. the AUC of 0.908 (95% CI 0.851-0.965, p < 0.001) for D-dimers.…”
Section: Discussionsupporting
confidence: 93%
“…However, determination of circulating vasopressin is technically challenging and unfeasible in emergency scenarios; blood copeptin (the C-terminal portion of vasopressin), on the other hand, may be used as a surrogate marker for the activity of vasopressin [13]. High copeptin levels have been found in myocardial infarction, heart failure and several studies have shown that it may also play a role in PE [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The overall risk profile and mortality in our study population were similar with previous observational studies focusing on acute PE [ 16 , 17 ]. This allowed us to examine if BDNF levels may be used as predictors for PE evolution by comparing parameters already validated for risk stratification.…”
Section: Discussionsupporting
confidence: 87%
“…Copeptin is released into the circulation in cases of hemodynamic stress. Among these are acute coronary syndrome [16], heart failure [17], pulmonary hypertension [18], sepsis [19], and acute pulmonary embolism [20]. In addition, copeptin levels in the blood rise rapidly also when the inflammatory process develops.…”
Section: Discussionmentioning
confidence: 99%